Bond enhancement for BFRP bar in concrete by using a resin-filled FRP tube anchorage. (May 2022) - Wang, Qiang; Zhu, Hong; Zhang, Bai; Zhao, Yanbing; Li, Fangzheng
Abstract: A novel additional anchorage system made out of epoxy resin-filled FRP tubes was proposed for FRP bars in concrete. A total of 33 specimens were carried out via the direct pull-out test to investigate the effectiveness of the developed anchorage in enhancing the bond between BFRP bars and concrete. The investigated variables consisted of the bond length of FRP bar, anchorage length, and the anchorage spacing. Due to the improved bond transfer mechanism for BFRP bar in concrete by using the proposed anchorage, the bond indexes, including the initial bond stiffness, ultimate bond strength, and the residual bond strength, were found to have the maximum improvements of 165.1%, 39.7%, and 162.9%, respectively. In addition, two current bond stress-slip constitutive models for unanchored FRP bars were modified to simulate the pull-out process of the anchored BFRP bars with good accuracy.